TIME-COST TRADE-OFF ANALYSIS ON JETTY CONSTRUCTION PROJECT (CASE STUDY : INDONESIAN NAVY JETTY CONSTRUCTION PROJECT) - Raditya Novianto; Avando Bastari; Abdul Rahman (STTAL POSTGRADUATE - INTERNATIONAL CONFERENCE, 2020)
ABSTRACT The performance of a project can be assessed based on the aspects of time, cost, and quality. The project is said to be successful when it can achieve the goals in the form of these three aspects by the initial planning. But the reality on the ground, often project implementation is not following the plan, resulting in project delays. Contractors can overcome the delay through various methods of accelerating time. This study aims to determine the acceleration of time through the Time-Cost Trade-Off analysis on The Indonesian Navy Jetty Construction Project in Saumlaki (Phase I) by comparing alternative methods of overtime and additional manpower. The analysis was carried out by using a quantitative descriptive method. The data used is secondary data such as of related documents, Bill of Quantity, S Curve, work volume, list of wages, and a number of workers. The calculation results show that acceleration using overtime alternatives can reduce 18 days or 6.98% of the implementation duration with a reduction in costs of IDR. 1,220,546,167.00 of the total cost of implementation (efficiency 1.8%). Additional manpower can reduce the duration for 19 days or by 7.36% with a reduction of IDR. 1,076,481,972.00 (1.61% efficiency). So that in this study it was found that the alternative of working overtime was more efficient than the alternative of additional manpower. Keywords : Scheduling, PDM, Crashing,